Teachers' Efforts to Introduce Arabic Vocabulary Through Singing Methods in Kindergarten - Siti Nur Ajizah; Muhammad Zulkarnaen; Muhammad Yusuf (EDUJAVARE: International Journal of Educational Research, 2025)
Vocabulary learning of Arabic for early childhood at TK Handayani Awang Bangkal Barat is an important effort to equip the younger generation with foreign language skills and global insights. This study aims to identify the strategies, approaches, and teaching media applied by teachers in introducing Arabic vocabulary as well as analyzing supporting factors and obstacles encountered during the teaching and learning process. The research method used is qualitative, employing observation and interviews with teachers and students. The findings indicate that teachers use interactive approaches such as educational games, singing, and visual media like flashcards and videos to enhance children’s interest and understanding of the Arabic language. Internal factors such as student motivation and teacher competence, along with external factors like the availability of learning media, play a significant role in the success of vocabulary acquisition. This study recommends the development of enjoyable, adaptive, and age-appropriate teaching methods to improve the effectiveness of Arabic language learning at TK Handayani and other early childhood education institutions.